EFEKTIVITAS KOMBINASI TERAPI GUIDED IMAGERY DAN BIMBINGAN SPIRITUAL TERHADAP KECEMASAN PASIEN PRE OPERASI ANESTESI SPINAL DI RUMAH SAKIT IHC LAVALETTE - Rifqi Khomisul Abkari, Muhammad; Marsaid; Hidayah, Nurul; Ernawati, Naya (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Preoperative anxiety is a common response experienced by individuals who are about to undergo surgical procedures. Spinal anesthesia can trigger anxiety, particularly due to the pain caused by the insertion of the spinal needle in the back, which often leads to patient apprehension toward the procedure. Previous studies have not combined guided imagery therapy with spiritual guidance. This study aims to determine the effectiveness of the combination of guided imagery therapy and spiritual guidance in reducing preoperative anxiety among patients undergoing spinal anesthesia at IHC Lavalette Hospital. This research employed a quasi-experimental two-group pre-test post-test design. The sampling technique used was purposive sampling, involving 72 respondents divided into two groups: an intervention group and a control group. Anxiety levels before and after the intervention were measured using The Amsterdam Preoperative Anxiety and Information Scale (APAIS). The results showed that the intervention group's anxiety level was moderate before the combined therapy and decreased to mild afterward. In contrast, the control group maintained a moderate level of anxiety both before and after the test. Statistical analysis revealed a p-value of 0.000 (< Alpha = 0.05) in the intervention group and 1.000 (> Alpha = 0.05) in the control group. These findings indicate that the combination of guided imagery therapy and spiritual guidance is effective in reducing preoperative anxiety in patients undergoing spinal anesthesia at IHC Lavalette Hospital. Future research is encouraged to explore other experimental methods with larger sample sizes focusing on relaxation therapies to reduce anxiety in surgical patients.